Association between COMT Val158Met polymorphism and preeclampsia in the Chinese Han population. (1st October 2016) - Zhao, Xiaohua; Liu, Jingjing; Zhao, Cuisheng; Ye, Ping; Ji, Jing; Wang, Jingli; Song, Weiqing; Xu, Jine; Liu, Shiguo
ABSTRACT: Objective : Previous studies have been indicated that catechol-O-methyltransferase gene ( COMT ) might play a significant role in the development of preeclampsia (PE). Our study aims to investigate the association between polymorphism in COMT with the susceptibility to PE in Chinese Han women. Method : A total of 1028 PE patients and 1399 normal pregnant women were enrolled. We detected the genotyping of COMT Val158Met loci by the TaqMan allelic discrimination real-time PCR . Results : No significant difference in the genotypic and allelic distribution was found between the two groups (genotype: X 2 = 0.583, p = 0.747; allele:X 2 = 0.526, p = 0.468). Conclusion : The COMT Val158Met polymorphism might not be associated with PE in Chinese women.